2017
DOI: 10.1021/acsami.7b06304
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic, Superabsorbing Aerogels from Choline Chloride-Based Deep Eutectic Solvent Pretreated and Silylated Cellulose Nanofibrils for Selective Oil Removal

Abstract: Superabsorbents are highly appealing materials for use in cleaning up oil and chemical spills. However, the development of a low-cost, highly efficient superabsorbent remains a major challenge. This paper demonstrates a straightforward method of producing a cellulose nanofibril aerogel that is low-cost, ultralight, highly porous, hydrophobic, and reusable superabsorbing cellulose nanofibril aerogel from recycled waste fibers using a simple, environmentally friendly nanofibrillation treatment involving deep eut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
105
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(110 citation statements)
references
References 46 publications
3
105
0
2
Order By: Relevance
“…The O-H vibrational absorption peaks were near 1441.55 cm −1 and 1252.79 cm −1 . A comparison of Figures 5 and 6 revealed that the infrared absorption peak of the C-N stretching vibration of ChCl disappeared, signifying the movement of the C=O vibration absorption peak of oxalic acid toward a higher wave number direction (from 1693.67 cm −1 to 1747.56 cm −1 and 1958.85 cm −1 ) due to the strong electronegativity of Cl − and the induction effect [28]. The peak band narrowed and weakened, and the vibrational absorption peak of O-H disappeared, which implied that the intramolecular hydrogen bonds of ChCl and oxalic acid disappeared.…”
Section: Determination Of Regenerated Cellulose By Xrdmentioning
confidence: 98%
“…The O-H vibrational absorption peaks were near 1441.55 cm −1 and 1252.79 cm −1 . A comparison of Figures 5 and 6 revealed that the infrared absorption peak of the C-N stretching vibration of ChCl disappeared, signifying the movement of the C=O vibration absorption peak of oxalic acid toward a higher wave number direction (from 1693.67 cm −1 to 1747.56 cm −1 and 1958.85 cm −1 ) due to the strong electronegativity of Cl − and the induction effect [28]. The peak band narrowed and weakened, and the vibrational absorption peak of O-H disappeared, which implied that the intramolecular hydrogen bonds of ChCl and oxalic acid disappeared.…”
Section: Determination Of Regenerated Cellulose By Xrdmentioning
confidence: 98%
“…Recently, a low cost, highly porous, ultralight and hydrophobic HDES was synthesized (combined techniques of nanofibrillation, silylation, and freeze-drying) and the aerosol was capable of squeezing oil (superabsorbing agents) with an absorption capacity of 65-205 (g/g) [66]. The absorbed oil was recovered by mechanical squeezing and the aerosol could be used for about 30 cycles [66]. Since HDES uses low cost renewable raw materials, applying this economical solvent to mitigate environmental pollutants is a promising area for future research.…”
Section: Applications Of Hdes In Extractionmentioning
confidence: 99%
“…Chemical treatments are used to isolate cellulose fibres to generate nanocellulose. Existing chemical pretreatment techniques include acid hydrolysis [ 69 ], carboxylation [ 70 ], carboxymethylation [ 71 ], quaternization [ 72 ], sulphonation [ 73 ], ionic liquid [ 74 ], and solvent-assisted pretreatments [ 75 ].…”
Section: Reviewmentioning
confidence: 99%